2019
DOI: 10.1891/2158-0782.10.3.113
|View full text |Cite
|
Sign up to set email alerts
|

From Policy to Practice: Women's Experiences of Breastfeeding-Friendly Worksites, Part 2

Abstract: IntroductionMaintaining lactation after returning to work is imperative for overall breastfeeding success, yet mothers who return to full-time employment outside the home are unlikely to meet their breastfeeding goals. Breastfeeding-friendly worksites are one potential solution.MethodUsing semi-structured interviews with employees in one rural New England town (N = 18), we aimed to better understand the barriers and supports to continued lactation at “breastfeeding-friendly” worksites.ResultsFive key themes em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Nine publications (37,39,(45)(46)(47)(48)(49)(50)(51) reporting eight breast-feeding support programmes were cross-sectional studies, most of which participants had received an intervention. Three publications across two studies reported only qualitative results on women's breast-feeding experiences (40,41,52) . There were eight publications that represented multiple reports of four studies (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine publications (37,39,(45)(46)(47)(48)(49)(50)(51) reporting eight breast-feeding support programmes were cross-sectional studies, most of which participants had received an intervention. Three publications across two studies reported only qualitative results on women's breast-feeding experiences (40,41,52) . There were eight publications that represented multiple reports of four studies (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Both reports presented cross-sectional data on duration of breast-feeding; however, one was focused on breast-feeding duration for all participants (46) while the other described breast-feeding problems of participants and compared breast-feeding duration of employees with lactation problems against those experiencing no problems (45) . Finally, there were two reports of a qualitative study investigating women's experiences of breastfeeding-friendly workplaces (40,52) . The current study reported on women's experiences of returning to work with the findings separated into two papers, one focused on the translation of policy into practice (40) and the other focused on the findings related to physical environment (52) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations